2022
DOI: 10.3389/fpsyt.2022.940872
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study on emotion regulation strategy use in individuals with Williams syndrome, autism spectrum disorder and intellectual disability

Abstract: BackgroundIndividuals with neurodevelopmental disorders often have atypical emotion profiles, but little is known about how they regulate their emotions. While several studies have examined emotion regulation strategy use in autism spectrum disorder (ASD), only a few have included individuals with intellectual disability (ID) or focused on specific syndromes such as Williams syndrome (WS).MethodsA parent-reported survey launched during the first months of the COVID-19 pandemic allowed to exploratorily study em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…children with ASD with and without intellectual disability [45]. While this study revealed a significant difference between the two groups in focusing on the positive, neither group utilized this strategy very frequently.…”
Section: Plos Onementioning
confidence: 57%
See 3 more Smart Citations
“…children with ASD with and without intellectual disability [45]. While this study revealed a significant difference between the two groups in focusing on the positive, neither group utilized this strategy very frequently.…”
Section: Plos Onementioning
confidence: 57%
“…In addition, we also explored age related differences in the use and effectiveness of specific coping strategies among children with ASD. To our knowledge, this is an area that has been explored in only a few studies of individuals with ASD to date [ 22 , 30 , 45 ]. Finally, we conducted exploratory correlational analyses to evaluate the extent to which ratings of frequency and perceived efficacy for each coping strategies are related, an area which has not yet been studied in individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All items were rated again on a 5-point Likert Scale; for frequency: 1 (very rarely) to 5 (very frequently); and for efficacy: 1 (not efficient) to 5 (very efficient). In total there were 14 items, which focused on maladaptive and adaptive ER strategies and cognitive and behavioural strategies to capture the relative strengths of each group (see 61 for examination of ER strategies use during COVID-19 for a range of neurodevelopmental populations including individuals with WS, but not for DS. Similarly that study did not examine efficacy of ER strategies which the present study furtherly explores).…”
Section: Methodsmentioning
confidence: 99%